Innovation of a Flattening Tool for Optimizing the Water Hyacinth Weaving Process at Maeswara Basket: A Preliminary Study and Technology Implementation - Kholifah, Nur; Triyanto; Elvera, Resi Sepsilia; Nurtanto, Muhammad; Eko Wibowo, Aris; Mutohhari, Farid; satya, Danang; Cintiara Kinanti, Tabita (Universitas Pendidikan Ganesha, 2024)
Maeswara Basket faces problems with manual flattening tools that are ineffective in producing crafts from water hyacinth fibre. The proposed solution is developing a flattening tool by considering ergonomics, work safety, speed settings, and primary controls features. This study uses a community-based research (CBR) approach with five stages: problem identification, literature analysis, design planning, manufacturing, and evaluation. Six people assessed the flattening tool based on ease of use, process efficiency, quality of results, and overall evaluation using a Likert scale of 1-5. The results showed that the tool met important criteria such as ergonomics, ease of operation, flattening speed, thickness consistency, quality of results, and component durability, with scores ranging from 4.3 to 4.8 out of 5.0, categorized as